Improvement of Water Hyacinth (Eichhornia crassipes) Quality as Animal Feed through Fermentation Using Rumen Microbes with the Addition of Molasses - Desi Susanti; Suci Rahmi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2022)
One of the potential alternative feed ingredients as animal feed is water hyacinth. However, the low quality and palatability cause water hyacinth not being liked by ruminants. One way to improve the quality of water hyacinth is using controlled technology involving rumen microbes. The purpose of the study was to determine the level of addition of molasses and fermentation time in improving the quality of water hyacinth using rumen microbes through the test parameters for crude protein and crude fiber content. This study used a completely randomized design (CRD) with factorial patterns with molasses levels, namely M1 = 5%, M2 = 10%, M3 = 15%, and fermentation time consisting of T1 = 7 days, T2 = 10 days, T3 = 13 days . Each experimental design was repeated 3 times to form 27 experimental units. Data were analyzed using variance, if there was a significant treatment effect (P<0.05), followed by the HSD test on the average treatment. The results showed that the highest crude protein content was 14.23% in the M2T3 treatment (10% molasses level with 13 days of fermentation time) (P<0.05) while the lowest crude fiber was 14.55% in the M3T2 treatment (15% molasses level with a dangerous time) 10 days). This treatment was significantly different (P<0.05) from the other treatments. The results of the study concluded that the addition of 10% molasses for 13 days of brewing time could increase the crude protein content in water hyacinth fermented using rumen-filled microbes.and the lowest decrease in crude fiber was at 15% molasses level with 10 days of fermentation.